Silk-derived carbon nanosheets for transparent conducting electrodes on flexible substrates - Cho, Se Youn; Abdulhafez, Moataz; Tomaraei, Golnaz Najaf; Lee, Jaegeun; Bedewy, Mostafa (Royal Society of Chemistry, 2026)
Transparent conducting films (TCFs) were fabricated through the transformation of silk fibroin (SF), a renewable natural biopolymer, into carbon nanosheets (CNSs) via a catalyst free carbonization process. By adjusting the SF concentration, spin coating rate, and heat treatment temperature, the thickness of the CNS films was tuned from 3.7 to 38.8 nm, while maintaining uniform and smooth surfaces with Ra values between 0.28 and 0.62 nm. Structural analyses showed that pseudo-graphitic nanodomains gradually developed as the heat treatment temperature increased, and these changes directly influenced the optical and electrical properties. The optimized CNS films exhibited an optical transmittance of up to 95.7% at 550 nm and an electrical conductivity of 4.4 x 102 S cm-1, achieving a balanced combination of transparency and conductivity comparable to other solution-processed carbon electrodes. This study provides a scalable and sustainable method for producing ultrathin and flexible carbon-based TCFs and offers clear guidance on the relationships among processing conditions, structural features, and the resulting material properties using silk fibroin as a renewable precursor.